Start with the trouble : poems - Donaghy, Daniel, 1970- (Book collections on Project MUSE., 2009)
Daniel Donaghy was raised in Philadelphia and is the author of Streetfighting, a Paterson Poetry Prize finalist. He is assistant professor of English at Eastern Connecticut State University and has received artist grants from the Connecticut Commission on Culture and Tourism and the Constance Saltonstall Foundation.